2016
DOI: 10.1016/j.fertnstert.2016.07.1093
|View full text |Cite
|
Sign up to set email alerts
|

Undergoing varicocele repair before assisted reproduction improves pregnancy rate and live birth rate in azoospermic and oligospermic men with a varicocele: a systematic review and meta-analysis

Abstract: Oligospermic and azoospermic patients with clinical varicocele who undergo VR experience improved live birth rates and PRs with IVF or IVF/ICSI. For persistently azoospermic men after VR requiring TESE for IVF/ICSI, VR improves sperm retrieval rates. Therefore, VR should be considered to have substantial benefits for couples with a clinical varicocele even if oligospermia or azoospermia persists after repair and ART is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(83 citation statements)
references
References 23 publications
0
74
0
2
Order By: Relevance
“…A recent meta‐analysis has demonstrated a strong trend toward improvements in natural pregnancy rate (PR) [OR = 1.69, 95% CI (0.951, 3.020), p = 0.073] and a statistically significant increase in live birth rates (LBR) [OR = 1.699, 95% CI (1.020, 2.831), p = 0.04] following intervention. Varicocelectomy has also been associated with a statistically significant increase in PR [OR = 2.3, 95% CI (1.022, 5.342), p = 0.044] and LBR [OR = 2.2, 95% CI (0.994, 4.904), p = 0.05] in men with non‐obstructive azoospermia (Kirby et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A recent meta‐analysis has demonstrated a strong trend toward improvements in natural pregnancy rate (PR) [OR = 1.69, 95% CI (0.951, 3.020), p = 0.073] and a statistically significant increase in live birth rates (LBR) [OR = 1.699, 95% CI (1.020, 2.831), p = 0.04] following intervention. Varicocelectomy has also been associated with a statistically significant increase in PR [OR = 2.3, 95% CI (1.022, 5.342), p = 0.044] and LBR [OR = 2.2, 95% CI (0.994, 4.904), p = 0.05] in men with non‐obstructive azoospermia (Kirby et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…This point gains its support from a very recent systematic review and meta-analysis, which revealed that varicocele repair improved pregnancy and live birth rates in oligospermic and azoospermic patients with varicoceles in couples undergoing ARTs, and improved sperm retrieval rates for persistently azoospermic men requiring testicular sperm extraction after varicocele repair (Kirby, Wiener, Rajanahally, Crowell, & Coward, 2016). This point gains its support from a very recent systematic review and meta-analysis, which revealed that varicocele repair improved pregnancy and live birth rates in oligospermic and azoospermic patients with varicoceles in couples undergoing ARTs, and improved sperm retrieval rates for persistently azoospermic men requiring testicular sperm extraction after varicocele repair (Kirby, Wiener, Rajanahally, Crowell, & Coward, 2016).…”
Section: Natural History and Treatment Strategy Of Infertility Withmentioning
confidence: 95%
“…Moreover, combination of the two approaches seems to produce some extent of synergistic effect. This point gains its support from a very recent systematic review and meta-analysis, which revealed that varicocele repair improved pregnancy and live birth rates in oligospermic and azoospermic patients with varicoceles in couples undergoing ARTs, and improved sperm retrieval rates for persistently azoospermic men requiring testicular sperm extraction after varicocele repair (Kirby, Wiener, Rajanahally, Crowell, & Coward, 2016). Factors may sway couples towards ICSI rather than varicocelectomy are advanced female reproductive age, fear of surgery and its potential complications, and the perception of comparable pregnancy outcome.…”
Section: Natural History and Treatment Strategy Of Infertility Withmentioning
confidence: 96%
“…Overall, the literature examining the effectiveness of IUI after varicocelectomy is suboptimal, with all existing studies being retrospective and underpowered. No meta-analysis has specifically examined the efficacy of IUI after varicocelectomy, owing to the dearth of studies and the poor quality of existing studies, as noted by Kirby et al in a 2016 metaanalysis examining the effect of ART on pregnancy and live birth rates after varicocele repair (36). Within the existing literature, after varicocele correction, the per-couple pregnancy rate after IUI ranges from 7.7% to 50%, making it a challenge to establish the true rate, and most of the studies that compare IUI success in men with treated versus untreated varicocele fail to find a statistically significant difference.…”
Section: Intrauterine Insemination After Varicocelectomymentioning
confidence: 99%